A comparative study of IT-application courses offered in the different library schools in Metro Manila - Pasicolan, Charles A.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
This is a study on the IT-application courses being offered at the different library schools in Metro Manila. Its objectives are: 1) know the reason or reasons behind the offering of IT-application courses in the different library schools in Metro Manila; 2) distinguish the similarities and differences of the IT-application courses offered in the different library schools; 3) determine the immediate changes upon the inclusion of IT-application courses; 4) find out whether the inclusion of IT-application courses has enhanced the course; and, 5) find out if the IT-application courses being offered by the different library schools comply with the standard set by the Philippine Association of Teachers of Library Science (PATLS).
The results of the study show that: 1) the offering and incorporation of IT-application courses are geared toward producing, not just librarians, but information professionals; 2) most of the library administrators, especially chief librarians, indicated that IT-application courses really helped in improving and enhancing the profession of librarianship; 3) majority of the library schools in Metro Manila follow or comply with the standards set by the Philippine Association of Teachers of Library Science in offering and incorporating IT-application courses; 4) there was an increase in the number of enrollees in the Centro Escolar University (CEU), Philippine normal University (PNU), and University of Santo Tomas (UST) upon the offering of IT-application course; 5) no distinction can be made in the Philippine Women's University (PWU) because the Bachelor of Library and Information Science (BLIS) degree program is just on its first year of implementing IT-application courses, and, 6) there's no way of determining whether IT-application courses affect the number of enrollees taking up Library Science in Manuel L. Quezon University (MLQU), National Teachers College (NTC) and University of Manila (UM) because these library schools do not offer IT-application courses as proposed by the Philippine Association of Teachers of Library Science.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information technology; Library schools -- Curricula -- Information technology -- Study and teaching. -- Philippines -- Manila Metropolitan Area